Energy balances and energy accounting : extract from Energy terminology : a multilingual glossary = Bilans et comptabilite de l'energie : Extrait de Terminologie de l'Energie : un lexique multilingue = Energiebilanzen und Energiebuchhaltung : Auszug aus Energie-Terminologie : ein mehrsprachiges Worterbuch = Balances y Contabilidad de la Energia : Separata de Terminologia de Energia : un glosario multilingue (Pergamon, 1985)
Energy Balances and Energy Accounting.